A HIGH SPATIAL RESOLUTION MID-INFRARED SPECTROSCOPIC STUDY OF THE NUCLEI AND STAR-FORMING REGIONS IN LUMINOUS INFRARED GALAXIES - Diaz-Santos, T; Alonso-Herrero, A; Colina, L; Packham, C; Levenson, N; Pereira-Santaella, M; Roche, P; Telesco, C (Institute of Physics Publishing, 2010)
We present a high spatial (diffraction-limited) resolution (∼0″.3) mid-infrared (MIR) spectroscopic study of the nuclei and star-forming regions of four local luminous infrared galaxies (LIRGs) using T-ReCS on the Gemini South telescope. We investigate the spatial variations of the features seen in the N-band spectra of LIRGs on scales of ∼100pc, which allow us to resolve their nuclear regions and separate the active galactic nucleus (AGN) emission from that of the star formation (SF). We compare (qualitatively and quantitatively) our Gemini T-ReCS nuclear and integrated spectra of LIRGs with those obtained with Spitzer IRS. Star-forming regions and AGNs show distinct features in the MIR spectra, and we spatially separate these, which is not possible using the Spitzer data. The 9.7 μm silicate absorption feature is weaker in the nuclei of the LIRGs than in the surrounding regions. This is probably due to the either clumpy or compact environment of the central AGN or young, nuclear starburst. We find that the [Ne II]12.81 μm luminosity surface density is tightly and directly correlated with that of Paα for the LIRG star-forming regions (slope of 1.00 ± 0.02). Although the 11.3 μmPAH feature shows also a trend with Paα, this is not common for all the regions and the slope is significantly lower. We also find that the [Ne II]12.81 μm/Paα ratio does not depend on the Paα equivalent width (EW), i.e., on the age of the ionizing stellar populations, suggesting that, on the scales probed here, the [Ne II]12.81 μm emission line is a good tracer of the SF activity in LIRGs. On the other hand, the 11.3 μmPAH/Paα ratio increases for smaller values of the Paα EW (increasing ages), indicating that the 11.3 μmPAH feature can also be excited by older stars than those responsible for the Paα emission. Finally, more data are needed in order to address the different physical processes (age of the stellar populations, hardness and intensity of the radiation field, mass of the star-forming regions) affecting the energetics of the polycyclic aromatic hydrocarbon features in a statistical way. Additional high spatial resolution observations are essential to investigating the SF in local LIRGs at the smallest scales and determining ultimately whether they share the same physical properties as high-z LIRGs, ULIRGs, and submillimiter galaxies and therefore belong to the same galaxy population. © 2010. The American Astronomical Society. All rights reserved.